[18F]FDG hypermetabolisms of the spleen and/or bone marrow: indirect signs of bacteremia. (20th July 2021) - Zanca, R; Bartoli, F; Lazzeri, E; Sollini, M; Slart, RHJA; Erba, PA
Abstract: Funding Acknowledgements: Type of funding sources: None. Aim: Recently hypermetabolisms of the spleen and/or bone marrow has been proposed as an indirect sign of infective endocarditis (IE), useful to reinforce the suspicion of IE in the absence of any other infectious, inflammatory, or malignant disease. The purpose of this study is to determine whether hypermetabolisms of the spleen and/or bone marrow are indirect signs of bacteremia rather than of IE, specifically. Materials and Method: In this work we retrospectively evaluated a series 240 patients who performed between January 2015 to December 2020 [18F]FDG PET/CT (Discovery 710 GE) for suspected infection. In particular, 80 pts had infections from different origin and a positive blood culture (PBC), 80 pts presented localized infection, but negative blood culture (IDBCN) and 80 pts were classified as definite IE (IED) according to the 2015 ESCcriteria. [18F]FDG SUVmax SUVmean in bone marrow, spleen and liver were measured drawind a 14 cm3 regions of interest (ROIs) positioned close to the centers of the spleen and of the right liver lobe, but excluding abscess and/or ischemic lesions., as previously described (Caroline Boursier et al. ; Jordy P.Pijl et al.). BM SUVmax and SUVmean was obtained from ROIs placed on the bodies of each of the five lumbar vertebrae, excluding any damaged vertebra. BM to liver SUV ratios (BLR) and spleen to liver SUV ratios (SLR) were calculated. Kruskal-Wallis tests and the Dunn's test procedure for multiple comparison were performed using JMP Statistical Discoverytm. Results: No significant difference among the three groups of SUVmax/mean or in SLR were found. Nevertheless, by grouping patients for the presence of positive blood culture (142 pts) or negative blood culture (98 pts), irrespectively from the final diagnosis a significant associations of SLR was found (p = 0.0070). No significant associations were found with BLR. Conclusions: Based on our data SLR in seems to represent an indirect signs of bacteremia, rather than IE.